Judges, litigants, and the politics of rights enforcement in Argentina (2018)
Under what conditions can courts produce political and social change? My claim is that courts can be most consequential when they act in concert with other actors to create political spaces for ongoing discussion and engagement with regard to rights. In explaining judicial impact, I focus on the novel and understudied oversight mechanisms-like follow-up committees and public hearings-That some assertive high courts deploy to monitor adherence to some of their rulings. The analysis is based on comparative case studies of two landmark socioeconomic rights cases handed down by the Argentine Supreme Court. I show that the deployment of oversight mechanisms can create institutional spaces where the court, elected leaders, and private and civil society actors converge to generate change, resulting in greater impact. © 2018 City University of New York. All rights reserved.